Screening of Pulmonary Function and Hs-CRP as Biological Responses to Dust Exposure and Industrial Work Environment among Crusher Workers - Maulana, Alfi; Tualeka, Abdul Rahim; Aini, Aini (Jurnal Biologi Tropis, 2025)
The packaging industry plays an essential role in the economy, involving various activities such as material crushing. Without proper control measures, workers in this sector are at risk of developing health problems, particularly those affecting lung function. Employees in the crusher area are continuously exposed to dust and airborne pollutants generated during the crushing process, which may lead to long-term respiratory disorders, including chronic obstructive pulmonary disease (COPD). This study aims to assess the lung function status of workers in the crusher area of a packaging industry and to analyze factors influencing respiratory health through basic pulmonary examinations and infection detection using high-sensitivity C-reactive protein (hs-CRP) tests. Lung function was evaluated using spirometry, and hs-CRP levels were measured from blood serum samples. The study involved 30 workers who worked approximately 40 hours per week. The results showed that 22 workers (73.3%) had normal lung function, while 8 workers (26.7%) experienced mild restriction. Meanwhile, hs-CRP examination revealed that 17 workers (56.7%) had elevated hs-CRP levels, and 13 workers (43.3%) were within the normal range.